Planned change interventions and discourses on social control - Silva, M. Gabriela (15th EBES Conference - Lisbon, 2015)
Purpose – This paper aims to contribute to a more complete understanding of planned change interventions on human processes by presenting a selective interdisciplinary history of training technologies and their contribution to the reproduction or transformation of discourses on social control in organizations. Design/methodology/approach – The author focuses on two broad assumptions on human nature to consider different training technologies and how these relate to competing discourses and thinking on social control in organizations. Findings – The study presents selective competing training technologies, which differ significantly in constructing models of human action and in (re)producing social control in organizations. Drawing on the simplistic notion of ‘homo economicus’, training technologies often focus on institutional design and the attendant formal control with positive incentives and rewards for performance. Archetypes of change and progress, which work out spontaneous personal relations or group norms/values, substantially influence group dynamics more via constraints and coercion than incentives and rewards. Practical implications – Considering that organizational change is often an intentional process made by interested parties towards improving effectiveness, then practitioners, scholars and managers need to be able to understand how training technologies lead to social control in order to avoid dynamics that destroy capacity. Originality/value – This paper offers a broader and more evaluative examination of planned change interventions on human processes, develops a vision that challenges the application of universal recipes to bring change in organizations, and discusses directions for future research.